Evidence-based clinical practice guidelines for peptic ulcer disease 2020 - Kamada, Tomoari; Satoh, Kiichi; Itoh, Toshiyuki; Ito, Masanori; Iwamoto, Junichi; Okimoto, Tadayoshi; Kanno, Takeshi; Sugimoto, Mitsushige; Chiba, Toshimi; Nomura, Sachiyo; Mieda, Mitsuyo; Hiraishi, Hideyuki; et al. (Journal of gastroenterology, 2021)
The Japanese Society of Gastroenterology (JSGE) revised the third edition of evidence-based clinical practice guidelines for peptic ulcer disease in 2020 and created an English version. The revised guidelines consist of nine items: epidemiology, hemorrhagic gastric and duodenal ulcers, Helicobacter pylori ( H. pylori ) eradication therapy, non-eradication therapy, drug-induced ulcers, non -H. pylori, and nonsteroidal anti-inflammatory drug (NSAID) ulcers, remnant gastric ulcers, surgical treatment, and conservative therapy for perforation and stenosis. Therapeutic algorithms for the treatment of peptic ulcers differ based on ulcer complications. In patients with NSAID-induced ulcers, NSAIDs are discontinued and anti-ulcer therapy is administered. If NSAIDs cannot be discontinued, the ulcer is treated with proton pump inhibitors (PPIs). Vonoprazan (VPZ) with antibiotics is recommended as the first-line treatment for H. pylori eradication, and PPIs or VPZ with antibiotics is recommended as a second-line therapy. Patients who do not use NSAIDs and are H. pylori negative are considered to have idiopathic peptic ulcers. Algorithms for the prevention of NSAID- and low-dose aspirin (LDA)-related ulcers are presented in this guideline. These algorithms differ based on the concomitant use of LDA or NSAIDs and ulcer history or hemorrhagic ulcer history. In patients with a history of ulcers receiving NSAID therapy, PPIs with or without celecoxib are recommended and the administration of VPZ is suggested for the prevention of ulcer recurrence. In patients with a history of ulcers receiving LDA therapy, PPIs or VPZ are recommended and the administration of a histamine 2-receptor antagonist is suggested for the prevention of ulcer recurrence.